Musical Mnemonics Training: Proposed Mechanisms and Case Example with Acquired Brain Injury. Issue 1 (24th April 2015) - Knott, David
Abstract: After an acquired brain injury, simple semantic, declarative memory tasks such as knowing one's address can be difficult to complete. Music's ability to extend and optimize shared neurologic pathways responsible for music perception, production, and memory processes makes rhythmic-melodic templates uniquely suited for declarative memorization tasks. Rhythm and melody have long been used to memorize information, and many have direct experience learning the letters of their alphabet using the familiar childhood song "Twinkle Twinkle." Therapeutic applications for musical mnemonics exist in both child and adult populations. Typically developing children, children with special needs, and those who have sustained neurologic injury or disease processes affecting memory may benefit from training using musical mnemonics. The purposes of this paper are to provide an overview of memory processing, review the research literature on music-mediated memory tasks in clinical populations experiencing impairments in memory, and describe suggested mechanisms for their action using the Rational-Scientific Mediating Model (Thaut, 2005 ). An intervention example utilizing the Transformational Design Model (TDM) will demonstrate how this technique can be implemented in a clinical setting.